Multi-material injection moulding - Goodship, Vannessa (Report (Rapra Technology Limited) ;, 2002)
Injection moulding is the most important of all the commercial methods of plastics processing. Many variations have been developed and one of the rapidly expanding fields is multi-material injection moulding. This is particularly important where processors are looking to gain technological advantages over rivals by adding value to products. Whilst tooling costs can be very high, cost savings can be made by eliminating assembly steps. This review looks at the many techniques being used, from the terminology to case studies. There are many issues involved in moulding different types of materials.